THE IMPACT OF ARTIFICIAL INTELLIGENCE ON MODERN COMPUTING - Abdusalomova Raykhona, Abduahakhatova Sitora (Ethiopian International Journal of Multidisciplinary Research, 2025)
In the last few decades, the field of computing has evolved at an unprecedented rate, with one of the most significant advancements being the development and application of Artificial Intelligence (AI). AI has revolutionized various sectors, including healthcare, education, finance, and even entertainment. In this article, we will explore how AI is transforming the landscape of modern computing, its key applications, and its future potential.